1999
DOI: 10.1159/000012768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guar Gum and Cellulose on Cecal Enzyme Activity and Cecal Short-Chain Fatty Acids in Young and Aged Mice

Abstract: The effects of cellulose or guar gum on cecal enzyme activity and cecal short-chain fatty acids (SCFAs) in young and aged mice were studied. Male Crj:CD-1 (ICR) mice were fed an MF diet for 4 (young mice) or 23 months (aged mice). The MF diet was then replaced with a semisynthetic diet supplemented with 5% guar gum or 5% cellulose. The mice were fed the guar gum or cellulose diet for 3 weeks. There was no significant difference in cecal content between the two diet groups. There were no significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…This process takes place in the liver and the conjugated compounds are excreted via the bile into the intestine and when they reach the colon they are usually excreted out of the body (Tamura et al, 1999). In our study, we have observed an increase in the β-glucuronidase activity in DMH administered rats.…”
Section: Discussionsupporting
confidence: 60%
“…This process takes place in the liver and the conjugated compounds are excreted via the bile into the intestine and when they reach the colon they are usually excreted out of the body (Tamura et al, 1999). In our study, we have observed an increase in the β-glucuronidase activity in DMH administered rats.…”
Section: Discussionsupporting
confidence: 60%
“…Beta-glucosidase activity was significantly lower in the aged mice fed the GG diet than in those fed the cellulose diet. [89] GG reduced steroid concentration considerably at all sites of the large intestine, which is consistent with their stool bulking effects. Hence, multicannulated pig may serve as a useful model of man in chemoprevention studies of colorectal cancer.…”
Section: Effect On Cell Proliferationsupporting
confidence: 76%
“…Tamura et al [14] showed lower ß-glucuronidase activity in mice fed 5% cellulose diet; Mallet et al [25] reported less reductive enzymes and ß-glucosidase by intake of 10% cellulose diet, and Jacobs [26] observed a decrease of experimental colon carcinogenesis compared with guar gum diet-fed mice. However, Shiau and Chang [27] did not find significant effects on bacterial cecal activity at high dose of the same dietary fiber.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was stopped by adding 0.5 ml (20%) trichloroacetic acid and p-aminobenzoic acid was measured by the Bratton-Marshall method [13]. Enzyme activities were expressed as nmol of transformed substrate/60 min/g cecal content [14].…”
Section: Measurement Of Enzyme Activitiesmentioning
confidence: 99%